2014
DOI: 10.1002/marc.201400333
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Anomalous Deformation of Poly(N‐Isopropylacrylamide) Gel Hybridized with an Inorganic Nanosheet Liquid Crystal Aligned by Electric Field

Abstract: Poly-(N-isopropylacrylamide) (PNIPA) hydrogel films doped with uniaxially aligned liquid crystalline (LC) nanosheets adsorbed with a dye are synthesized and its anomalous photothermal deformation is demonstrated. The alignment of the nanosheet LC at the cm-scale is easily achieved by the application of an in-plane or out-of-plane AC electric field during photo-polymerization. A photoresponsive pattern is printable onto the gel with μm-scale resolution by adsorption of the dye through a pattern-holed silicone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…[77][78][79] In recent work, Inadomi et al prepared hydrogel films that were doped with uniaxially ordered liquid crystalline nanosheets that had adsorbed a dye (Figure 4c). [80] In top-and side-images of the ordered nanocomposite hydrogel, uniform interference colors of blue or yellow were observed, which demonstrated that the liquid crystalline nanosheets were aligned along the applied electric field. In addition, their hydrogel showed not only anisotropic shrinkage but also anomalous expansion in a specific direction; this behavior contrasted with that of the conventional composite hydrogel with unordered structure, which only showed isotropic swelling/deswelling that was induced by heat.…”
Section: Electric Fieldsmentioning
confidence: 96%
“…[77][78][79] In recent work, Inadomi et al prepared hydrogel films that were doped with uniaxially ordered liquid crystalline nanosheets that had adsorbed a dye (Figure 4c). [80] In top-and side-images of the ordered nanocomposite hydrogel, uniform interference colors of blue or yellow were observed, which demonstrated that the liquid crystalline nanosheets were aligned along the applied electric field. In addition, their hydrogel showed not only anisotropic shrinkage but also anomalous expansion in a specific direction; this behavior contrasted with that of the conventional composite hydrogel with unordered structure, which only showed isotropic swelling/deswelling that was induced by heat.…”
Section: Electric Fieldsmentioning
confidence: 96%
“…In particular,m icropatterned electrodes enable the precise positioning of oriented nanofillers in thin hydrogel films to afford hierarchical structures that are generally difficult to access by other methods.Itshould be noted that electric fields possibly cause undesired electrochemical decomposition and electrophoresis.T oa void these problems,t he conditions,s uch as voltage, current frequency, and sample thickness,o ften need to be optimized. Thus far, electric orientation has been used for the synthesis of anisotropic hydrogels containing functionalized carbon nanotubes, [42][43][44] clay nanosheets, [45,46] silver nanowires, [47] silk nanofibers, [48] and barium titanate particles. [49] Similar to electric fields,m agnetic fields can be used to afford anisotropic hydrogels,w here an anofiller is oriented with its easy magnetization axis parallel or antiparallel to the applied magnetic field (Figure 2b).…”
Section: Hydrogels With Oriented Nanofillersmentioning
confidence: 99%
“…[18,[88][89][90][91] Ty pically,a na queous solution of an anionic polymer is filled in ac ontainer, and one end of the container is put in contacted with an aqueous solution containing multivalent cations so that the cationic ions diffuse directionally.A st he diffusion proceeds,t he anionic polymer chains are crosslinked anisotropically to afford ah ydrogel with an oriented polymer-chain network. Va rious anionic polymers have been used as components of such networks, shear forces collagen nanofibers [23] cellulose nanofibers [24] lamellar bilayer [25][26][27] imogolite nanotubes [33] graphene oxide [34] clay nanosheets [32] graphene oxide [34] -s ynthetic peptide nanofibers [19,20] collagen nanofibers [21,23] electric fields silk nanofibers [48] clay nanosheets [46] -f unctionalized carbon nanotubes [42][43][44] silk nanofibers [48] magnetic fields barium ferrite particles [53,55] graphene oxide [70] titanate nanosheets [71] alumina platelets [60] titanate nanosheets [72] magnetite particles [52] micelles [66,67] -Section 2.2 Hydrogels with oriented polymerchain networks compression or stretching alginate/acrylic polymer [81] acrylic polymer [82] poly(vinyl alcohol) [84,85] -s cleroglucan [87] poly(vinyl alcohol) [80] collagen nanofibers…”
Section: Hydrogels With Oriented Polymer-chain Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, synthetic hydrogels usually have an isotropic and amorphous structure, resulting in the absence of anisotropic optical and mechanical properties. Inspired by the nature, there are many efforts to develop anisotropic hydrogels by different strategies, including molecular self‐assembly, electric/magnetic field‐directed orientation, and diffusion‐induced orientation, to form ordered structures before or during the gelation process. For instance, Thomas and co‐workers prepared photonic hydrogels by molecular self‐assembly of a block copolymer to form a uniform lamellar structure, which was subsequently fixed by chemical cross‐linking .…”
Section: Introductionmentioning
confidence: 99%